Caveats and criteria: intercultural courtships of shengnü ('leftover women') and Western men in urban China. (1st November 2021) - To, Sandy
Abstract : The phenomenon of shengnü ('leftover women') has attracted much attention in recent years. Many of these single, never-married women have adopted the alternative partner choice strategy of choosing Western men, in the belief that they would be more open-minded about their accomplishments than patriarchal Chinese men. In this study of 17 shengnü 's intercultural courtship experiences in Shanghai, it was found that they faced many caveats. In reality, it was difficult for them to find equally accomplished Western men who were looking for serious relationships. Those who were high-flying executives were often orientalist or licentious, and those who were unambitious were resented and scorned (by the women). Economic criteria aside, one key criterion that the Western men had to fulfil was to know Chinese in order to communicate with the women's parents. The topic of intercultural courtships brings to light the haigui (overseas returnee) identity of the shengnü who straddle the world of a global cosmopolitan professional elite, and the world of a developing Chinese economy where traditional features like filial piety and guanxi (social connections) still endure.